Проблеми спонтанної натуралізації інтродукованих рослин у дендрологічному парку “Олександрія” НАН України - Galkin, S.I.; Doiko, N.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The spontaneous naturalization of introduced plants species increasingly causes concern in recent years, sometimes it poses a real threat to the existence of native plant species. In the State Dendrological Park Olexandria of the NAS of Ukraine for the first time was made an analysis of the adventive fraction of vegetation, which is capable of spontaneous spreading. As of 2015 it is registered 175 species from 56 families and 135 genera, which were naturalized in the conditions of the park, that makes 18.5 % of the total number of introduced species. Over the life forms they are the trees (19 species), bushes (15), woody vines (11), herbaceous plants (120 species). It was established that most of the species (72.6 %) on the territory of the park are spread by the seed method. 111 (63.4%) from the studied species capable of spontaneous distribution of natural phytocenoses. In areas with agro-technical cultivation were recorded 22 (11.4 %) species. There is the list of 46 species that are a danger to local flora.